Effect of transcutaneous electrical nerve stimulation therapy on condylar position and myofascial pain in patients with temporomandibular joint disorders-A pilot clinical trial - R Rebekah; R Navaneethan; KS Nagachandran (Wolters Kluwer Medknow Publications, 2024)
OBJECTIVE: Temporomandibular joint disorders (TMD) are a type of disorder that affects the temporomandibular joint, muscles, and nerves leading to persistent facial pain. Transcutaneous electrical nerve stimulation (TENS) therapy is an alternative treatment for pain relief in TMD patients. The aim of the study was to assess the condylar position changes and pain levels occurring in TMD patients after TENS therapy. MATERIALS AND METHODOLOGY: According to the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) criteria, a total of seven patients with TMD were included in this study. Routine diagnostic investigations were taken for each patient along with joint vibration analysis (JVA), electromyography (EMG), and a cone beam computed tomography (CBCT) at rest position. Using the Dolphin software (version 11.95), the temporomandibular joint spaces were measured on the CBCT for the right and left sides individually for each patient. These patients were then subjected to TENS therapy, and an EMG reading was taken post-TENS therapy to evaluate the effect on muscle strain. A CBCT was taken after the TENS therapy to assess its effect on the condylar position. The statistical significance of the pre- and post-temporomandibular joint spaces and the EMG readings post-TENS therapy were assessed using paired t-tests, respectively. RESULTS: There was a change in the anterior, middle, and posterior dimensions observed radiographically, before and after TENS. However, the results were found to be statistically significant only in the anterior region on the right joint space (P = 0.03) and posterior region of the left joint space (P = 0.04). CONCLUSION: TENS therapy has been found to bring about a change in the condylar position and pain intensities by relieving inadvertent muscle activity in the temporomandibular region. Therefore, further studies with larger sample sizes and control are required to fully ascertain the role of inadvertent muscle activity on the TMJ.